Marine n‐3 fatty acids and cognitive change among older adults in the VITAL randomized trial. (31st December 2021) - Kang, Jae Hee; Vyas, Chirag M; Okereke, Olivia I; Ogata, Soshiro; Albert, Michelle; Lee, I‐Min; D'Agostino, Denise; Buring, Julie E; Cook, Nancy R; Grodstein, Fran; Manson, JoAnn E
Abstract: Background: High intake of marine omega‐3 (n‐3) fatty acids has been associated with lower risk of cognitive decline; however, few large‐scale, long‐term randomized trials have been conducted. We evaluated n‐3 supplementation (1 gram/day, including 840 mg of EPA + DHA) and change in cognitive function over 2‐3 years. Method: Community‐dwelling participants aged 60+ years (mean[SD]=70.9[5.8]y) in the Vitamin D and Omega‐3 Trial (VITAL) were included: 3424 had cognitive function assessment by phone (VITAL‐Cog; 8 neuropsychological tests; mean follow‐up=2.8 years) and 794 were evaluated in‐person at the Harvard Clinical and Translational Science Center (CTSC‐Cog; 9 neuropsychological tests; mean follow‐up=2.0 years). The primary, pre‐specified outcome was a global composite score (average z‐scores across all tests) of change over two assessments. We used multivariable‐adjusted linear mixed models and meta‐analyzed the results for the two settings. Result: We observed no significant effect of n‐3 supplementation on the global composite score: the mean difference in annual rate of change for the n‐3 versus placebo group was ‐0.01 standard units (95% CI:‐0.02, 0.003) in VITAL‐Cog and ‐0.002 (95% CI:‐0.04, 0.03) in CTSC‐Cog; the pooled mean difference was ‐0.01 (95%CI:‐0.02, 0.003; p=0.15). For secondary outcomes of change in verbal memory, executive function/attention and general cognition, we observed null results to trends of adverse associations with n‐3 treatment versus placebo that were not statistically significant after multiple‐testing correction. In pre‐specified secondary analyses, we observed no significant interaction of the intervention with baseline plasma omega‐3 fatty acid levels for the global composite score (pooled p‐interaction=0.37). Conclusion: Marine n‐3 supplementation (1 gram/day) did not confer cognitive benefits over 2‐3 years in community‐dwelling older adults.